Hukum Keluarga Islam di Tengah Arus Globalisasi: Dampak Media Sosial Terhadap Pola Pernikahan dan Relasi Keluarga Muslim: Islamic Family Law in the Midst of Globalization: The Impact of Social Media on Muslim Marriage Patterns and Family Relations - Wahyudi Wahyudi; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani (Res Nullius Law Journal, 2025)
This article examines the impact of social media as a primary instrument of globalization on the socio-legal norms of Islamic family law (fiqh al-usrah). It argues that digital platforms have created a new public sphere that significantly transforms the social construction and practice of Islamic marriage and family relations. Using a socio-legal research method that analyzes classical jurisprudence (fiqh) texts, contemporary legal compilations, and empirical phenomena from social media, this study focuses on three critical areas: the transformation of matchmaking (khiṭbah) into a digital "marriage market," the spectacularization of dowry (mahr) and wedding ceremonies (walimah) as displays of status, and the reconfiguration of spousal and parent-child relationships through the logic of online self-presentation and conflict airing. The findings indicate that social media acts as a disruptive force, generating tensions between static legal interpretations and evolving social realities. It necessitates a contextual reinterpretation of Islamic family law to address new challenges related to privacy, financial pressure, and digital literacy. The article concludes that navigating this digital landscape requires a balanced approach that upholds the core objectives of Islamic law (maqāṣid al-sharīʿah) while constructively engaging with the dynamics of the networked society.   Artikel ini menganalisis dampak media sosial sebagai instrumen utama globalisasi terhadap norma sosial-hukum dari hukum keluarga Islam (fiqh al-usrah). Argumen utama menyatakan bahwa platform digital telah menciptakan ruang publik baru yang mentransformasi konstruksi sosial dan praktik dari perkawinan dan relasi keluarga Islam. Dengan menggunakan metode penelitian sosio-legal yang mengkaji teks-teks fikih klasik, kompilasi hukum kontemporer, serta fenomena empiris dari media sosial, studi ini berfokus pada tiga area kritis: transformasi lamaran (khiṭbah) menjadi "pasar pernikahan" digital, spektakularisasi mahar (mahr) dan walimah sebagai pertunjukan status, serta rekonfigurasi relasi suami-istri dan orang tua-anak melalui logika presentasi diri dan pengungkapan konflik daring. Temuan penelitian menunjukkan bahwa media sosial berfungsi sebagai kekuatan disruptif yang menciptakan ketegangan antara interpretasi hukum yang statis dan realitas sosial yang terus berkembang. Hal ini memerlukan reinterpretasi kontekstual atas hukum keluarga Islam untuk menjawab tantangan baru terkait privasi, tekanan finansial, dan literasi digital. Artikel menyimpulkan bahwa navigasi di lanskap digital ini membutuhkan pendekatan seimbang yang menegakkan tujuan utama syariat Islam (maqāṣid al-sharīʿah) sekaligus secara konstruktif terlibat dengan dinamika masyarakat jaringan.